Pembelajaran Matematika Dasar Menyenangkan Pada Anak Berkebutuhan Khusus dengan Media Pembelajaran Simple Multiplication Elektrik - Ratna Herawati Ratna; Robby Rachmatullah; Prihanto (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Learning as a guidance process in the learning process. Children with special needs require their own methods in learning because they are handled differently from regular students. Regarding basic mathematics learning, most educators at SLB B-C YPPS Ngemplak Boyolali lack understanding about quality learning assisted by technology-based learning media. This activity purpose is to improve classroom management, the educator’s competence in implementing deep learning through learning innovations by utilizing technology-based learning media. From a social perspective, this activity can increase the knowledge of students with special needs in learning basic mathematics fun with technology-based learning media so that attention is increased. Training and mentoring are provided for educators and students in terms of innovations in learning basic mathematics fun with the use of technology-based learning media. The method used in this activity is SMART goals. The results of this activity are, there is an improvement in classroom management with the implementation of deep learning assisted by technology-based learning media